El fundamento de los principios jurídicos: una cuestión problemática. (2016)
This article aims to analyze the influence the normative category of legal principles has had in the Colombian constitutional law and how it has transformed the theory and practice of contemporary constitutional law. In addition, a forgotten issue in the contemporary theory of legal principles arises: the ultimate foundation of the normative force of the principles. Thus, it is offered as a final answer, barely glimsed, that human dignity is the foundation of the ius constitutional requirements contained in legal principles.